Antibody-independent complement activation by myelin via the classical complement pathway (The Rockefeller University Press, 1982)
Murine or rabbit whole brain homogenates were shown to activate human complement via the classical pathway by an antibody-independent reaction. This activity required Ca++ ions. Anticomplementary activity in fractionated murine brain was found to reside in the myelin fraction and in purified myelin. It was absent, however, both from highly purified myelin basic protein (MBP) and from the MBP-free residue. Because purified MBP is a monomer and this protein exists in brain tissue largely as a dimer, the ability of the cross-linked form of MBP to activate complement was investigated. MBP, dimerized with difluorodinitrobenzene, was highly anticomplementary. The murine brain, inactive when taken from the newborn mouse, was shown to first acquire the capacity to activate complement at 7 d after birth. This finding is consistent with the report that the synthesis of myelin protein has been shown to be initiated in murine brain 8 d after birth. Complement activation by MBP could play an important role in the pathological changes observed in neurological disorders.